Approximate solutions to the conformable Rosenau-Hyman equation using the two-step Adomian decomposition method with Pade approximation - Akgul, Ali; Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (Wiley, 2020)
This paper adopts the Adomian decomposition method and the Pade approximation techniques to derive the approximate solutions of a conformable Rosenau-Hyman equation by considering the new definition of the Adomian polynomials. The Pade approximate solutions are derived along with interesting figures showing both the analytic and approximate solutions.
Keywords: Adomian decomposition method; conformable Rosenau-Hyman equation; Pade approximation